Information-didactic base of preparing university teachers for working-out and use of innovative pedagogical technologies - Marta I. Diri; Olga V. Yusupova; Valentin N. Mikhelkevich (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article discusses information-didactic base of preparing university teachers for working-out and use of innovative pedagogical technologies in the system of additional education. The high relevance of the problem of introducing innovative educational technologies into the educational process of universities is substantiated. The analytical review of Russian and foreign scientific publications and teaching aids on the issue has been made. In the world scientific literature direct studies on this topic have not been identified. According to the analysis, nowadays the law of Russian Federation supports projects ofworking-out, developing, and improvingof new technologies in the field of education for training new generation specialists.In this article the authors’ interpretation of the definition of university teachers “readiness” for working-out and use of innovative pedagogical technologies is given. That is defined as an integrative phenomenon consisting of several functional components. Informational and didactic base for training university teachers to develop and use innovative pedagogical technologists is worked out and presented. This information and didactic base provides a staged solution of local problems, that is, the formation of every readiness` component. Organizational forms of training university teachers for working-out and use of innovative pedagogical technologies in which this training may be implemented are proposed. The results of the study can be used by managers, methodologists and teachers in the system of university teachers` advanced training, as well as by teachers in the mode of self-study.